Bowlby's five therapeutic tasks: bringing them up to date for children - Simon R. Wilkinson (BJPsych Bulletin, 2024)
Bowlby remained attached to his psychoanalytic roots and conceptualised treatment in terms of one-to-one relationships, albeit acknowledging the need for a family formulation. Bowlby's five therapeutic tasks were never adapted to the current understanding of working with the relationships fostering the development and maintenance of children's attachment strategies. This paper goes through each of Bowlby's five tasks and adapts them to our current understanding of development, with consequences for prioritising family approaches, rather than a secure base alone with a therapist. In doing so I will review the process of achieving security, seeing it as more similar to an allostatic process than a state of homeostasis.